ANALISIS PERTUMBUHAN EKONOMI SEKTORAL DAN SEKTOR EKONOMI UNGGULAN DI KABUPATEN JEMBRANA - Aliffianti Nuril Islam; Wahyu Hidayat Riyanto; Yunan Syaifullah (Jurnal Ilmu Ekonomi JIE, 2019)
This research aims to determine the level of economic growth and leading economic sectors in Kabupaten Jembrana. This study uses economic growth analysis tools, SLQ and DLQ, shift share and typology classifications using secondary data from Badan Pusat Statistik (BPS). Based on the results of the study it can be concluded that the level of economic growth in Kabupaten Jembrana in 2013-2017 decreased and included in the category of leading sectors were the Agriculture, Forestry and Fisheries, Construction, Wholesale and Retail Sectors; Car dan Bicycle Repair, Transportation and Warehousing, Information and Communication and Real Estate. The results of the shift share analysis show that the economic sector classified as the mainstay or competitive sector is the Agriculture, Forestry and Fisheries and Transportation and Warehousing sectors. The results of the Klassen typologi analysis show that the classification of developing sectors includes Wholesale and Retail Trade; Car and Bicycle Repair, Transportation and Warehousing, Provision of Accommodation and Eating Drinking and Information and Communication.